The limits of freedom in tourism - Piotr Majdak; Jakub Mosz (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The subject of the article is a reflection devoted to the limits of freedom in tourism, focusing on the attitudes of tourists moving on the verge of acceptable and unacceptable behavior from a social and moral point of view. The attitude of tourists has the form of egoistic hedonism that can take the form of natural behavior for tourism practice, be gentle and acceptable or take the form of border behavior, violating moral and legal norms, not accepted from a moral point of view. The analysis of these borderline situations shows the reality of the issue of the limits of freedom in tourism and their cultural conditioning.